Pengaruh Permainan Balok Susun Terhadap Kemampuan Berpikir Kreatif Siswa Kelas VII - Hilda Andriani; Tanti Jumaisyaroh Siregar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
The purpose of this study was to measure students' creative thinking skills using stacking blocks as media. The research method used is a quantitative method. The research sample consisted of 60 students from class VII-2 and VII-3. The instrument used is a test of the ability to think creatively and use stacking blocks as media. Based on the results and discussion conducted, the average value in the experimental class is higher than the average value in the control class. By using stacking blocks as media, students can improve their creative thinking skills. Out of a total of 60 students tested, only 58.33% of students had a low level of creative thinking. Of the four indicators of the ability to think creatively there are various categories such as poor, sufficient, good, and very good. In the learning process, the teacher can evaluate the level of students' creative thinking by using various types of media, including constructing blocks, and the teacher can channel their creativity in the learning process.